MUHAMMAD SAW SEORANG FEMINIS - Muhandis Azzuhri (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
Feminism point of view - as a modern deliberation of IXth century, coming from western is not a peculiar entity for eastern (read : Islam). The figure of Rasululloh SAW presents that Islam messenger has shown humanist characteristics for females particularly on behalf of wives and Islamic females in earlier era of Islam by respecting gender equality therefore the rights of politics, economy and social between males and females are regarded same, there are no discriminations just by the differences in sex and gender. Perspectives and morality characters shown by Rasululloh SAW to females in this writing is completed by performing explorations through historical and hadists texts concerning females around the Prophet and his best friends. Based on the analysis, it can be concluded that the Holy Prophet Muhammad SAW is a profile of Prophet having feminist, non discriminative, humanist and universal ways of thinking.